Financial Management Analysis Of Islamic Boarding Schools (Case Study Of PP Sunan Drajat Lamongan) - Sirojudin Munir, Akhmad (Mudir : Jurnal Manajemen Pendidikan, 2024)
Abstract: This research aims to analyze the financial management of the Sunan Drajat Lamongan Islamic Boarding School as a case study. Financial management in educational institutions such as Islamic boarding schools has an important role in supporting operational continuity and development of educational programs. With a focus on PP. Sunan Drajat Lamongan, this research includes an analysis of the financial structure, fund management, and financial policies implemented by the institution. The research method used is qualitative research with a case study approach. Data was obtained through interviews with related parties, observation, and analysis of documents related to Islamic boarding school finances. The results of this research provide an overview of PP's financial health. Sunan Drajat Lamongan, including the effectiveness of fund management and the financial strategies implemented. The findings of this research can provide an important contribution in increasing understanding of Islamic boarding school financial management, especially in the context. PP. Sunan Drajat Lamongan. The practical implications of this research can provide recommendations for improvements or developments in certain aspects of Islamic boarding school financial management, so that they can support the achievement of educational goals and institutional sustainability. Apart from that, this research can also be a reference for similar educational institutions in improving the efficiency and transparency of financial management.